Water-saving driven crop reallocation reduces irrigation energy demand in the mediterranean - Davide Danilo Chiarelli; Harsh Nanesha; Martina Sardo; Athanasios Ragkos; Maria Cristina Rulli (Global Food Security, 2025)

The economic performance of sheep pastoral systems in the Mediterranean: An analysis based on typologies - Dimitrios Skordos; Georgia Koutouzidou; Pasquale Arca; Giovanni Altana; Matteo Francioni; Marco Bianchini; Marisol Dar Ali; Alexandra Sintori; Sokratis Sokratous; Ante Ivankovic; Edmondo Suran; Nazan Koluman; et al. (Livestock Science, 2025)

Nature’s contribution to people provided by pastoral systems across European, African, and Middle East Mediterranean countries: trends, approaches and gaps - Graeme Dean; Matteo Francioni; Marco Toderi; Feliu López-i-Gelats; Laura Trozzo; Marta G. Rivera-Ferre; Antonello Franca; Giovanni M. Altana; Maria Karatassiou; Zoi M. Parissi; Eleni M. Abraham; Athanasios Ragkos; et al. (Regional Environmental Change, 2024)
Mediterranean pastoral systems are providers of a wide array of Nature’s Contribution to People (NCP). They are ‘complex systems’ characterized by limited resources and socio-economic dynamics currently threatened by climate and social changes. Despite a growing number of scientific articles dealing with NCP, there is a high risk that the existing literature has left out the complexity of such systems. In the light of ongoing social, economic, and climatic changes in the Mediterranean basin, neglecting the complexity of pastoral systems can lead to significant research biases, missing the priorities affecting the stability and continuity of such systems. A combination of frameworks of analysis provided by the Millennium Ecosystem Assessment and by the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services was applied to understand if and to what extent the complexity of Mediterranean pastoral systems has been considered in the available literature. Most of the 126 papers report studies conducted in the European Union zone (102 papers), with the majority in Spain (50). Fewer studies have been conducted in the Middle East (15 papers) and Africa zones (9 papers). Despite results confirming the importance of pastoral systems as providers of NCP, most of the eligible papers focused on regulating NCP. A lack of a multisectoral approach and integration of knowledge suggests that the complexity of Mediterranean pastoral systems has been overlooked by researchers. The creation of ‘hybrid knowledge’ bridging the expertise of different stakeholders could be the key ingredient to properly address the complexity of Mediterranean pastoral systems.

How valuable are the ecosystem services of local animal breeds? The case of Kalaritiko sheep in Greece - Dimitrios Skordos; Athanasios Ragkos; Pavlos Karanikolas; George Vlahos (Livestock Science, 2024)

Assessing the effect of soil testing on chemical fertilizer use intensity: An empirical analysis of phosphorus fertilizer demand by Irish dairy farmers - Evgenia Micha; Andreas Tsakiridis; Athanasios Ragkos; Cathal Buckley (Journal of Rural Studies, 2023)

Revealing the profile of economically efficient mussel farms: a restricted data envelopment analysis application - Alexandros Theodoridis; Athanasios Ragkos; Georgia Koutouzidou (Aquaculture International, 2020)

Scenarios of optimal organization of sheep and goat transhumance - Athanasios Ragkos; Stavriani Koutsou; Maria Karatassiou; Zoi M. Parissi (Regional Environmental Change, 2020)

Educational needs and perceptions of the sustainability of precision agriculture: survey evidence from Greece - Georgios Kountios; Athanasios Ragkos; Thomas Bournaris; Georgios Papadavid; Anastasios Michailidis (Precision Agriculture, 2018)

Technical efficiency measurement of mussel aquaculture in Greece - Alexandros Theodoridis; Christos Batzios; Athanasios Ragkos; Panagiotis Angelidis (Aquaculture International, 2017)

Using a functional approach to wetland valuation: the case of Zazari–Cheimaditida - Athanasios Ragkos; Asimakis Psychoudakis; Argiro Christofi; Alexandros Theodoridis (Regional Environmental Change, 2006)